1996
DOI: 10.1093/bja/76.1.66
|View full text |Cite
|
Sign up to set email alerts
|

A double-blind comparison of 0.25% ropivacaine and 0.25% bupivacaine for extradural analgesia in labour

Abstract: Ropivacaine is a new aminoamide local anaesthetic. Compared with bupivacaine, ropivacaine possesses a higher threshold for systemic toxicity and a high selectivity for sensory fibres. We have compared prospectively these two agents in a concentration of 0.25% for extradural analgesia in labour. A total of 104 parturients requesting extradural analgesia were randomized to receive either ropivacaine or bupivacaine. The women in the bupivacaine group required more top-up doses to maintain analgesia (median 3.0 vs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
29
0
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(32 citation statements)
references
References 30 publications
2
29
0
1
Order By: Relevance
“…However, in this study, intermittent injection rather than infusions were used for analgesia and the bupivacaine group needed more top-up injections than did the ropivacaine group. Both these studies showed 13,14 that ropivacaine, despite its lower potency, provided similar degree of analgesia as bupivacaine at comparable concentration.…”
Section: Discussionmentioning
confidence: 91%
“…However, in this study, intermittent injection rather than infusions were used for analgesia and the bupivacaine group needed more top-up injections than did the ropivacaine group. Both these studies showed 13,14 that ropivacaine, despite its lower potency, provided similar degree of analgesia as bupivacaine at comparable concentration.…”
Section: Discussionmentioning
confidence: 91%
“…An aliquot of 100 ml of sample was added to Iprindol 1 mg.l 21 (internal standard), 0.1 ml ammonium hydroxide and 50 ml N-butyl acetate into a Dreyer tube. The range of standards was 0.1± 2.0 mg.ml 21 for total ropivacaine and 0.02± 0.2 mg.ml 21 for unbound ropivacaine. The coefficients of variation were 6.5% (within assay) at 0.2 mg.ml 21 and 2.3% at 2.0 mg.ml 21 (within assay).…”
Section: Blood Samplingmentioning
confidence: 93%
“…Ropivacaine may therefore be expected to be less potent. However, clinical dose-finding studies have suggested a similar anaesthetic potency to bupivacaine, although with slightly different pharmacodynamic effects [7][8][9]. Higher concentrations of ropivacaine (0.5-1.0%), when given into the epidural space, have been found to provide equal sensory and motor blockade to similar concentrations of bupivacaine, but with a motor blockade of shorter duration [10][11][12][13].…”
mentioning
confidence: 99%